ACUTE GASTROENTERITIS (AGE) DUE TO VIBRIO CHOLERAE ELTOR OGAWA IN MUMBAI – A 5 YEAR STUDY - VAISHALI R. WABALE,; AMEETA A. JOSHI,; RENU S. BHARADWAJ,; ABHAY S. CHOWDHARY,; B. L. SARKAR, (International Journal of Pharma and Bio Sciences, 2016)
Vibrio cholerae erupted as leading, unpredictable, potent pathogen to the global fear of reemergence with an ability to cause epidemics and antibiotic resistance. Newer molecular and more discriminatory procedures helping epidemiologists to understand evolution, spread and emergence of newer variants. To study prevalence of V. cholerae and to identify current circulating biotype, serotype, phage type and changing pattern of antibiotic resistogram for epidemiological purpose. Hanging drop preparations (HDP) technique performed on all samples. Identified strains were serotyped using high titer antisera against O1, Ogawa, Inaba and O139. Phage typing by ‘Basu and Mukherjee' & ‘New Scheme' performed. Antibiogram had done using modified Kirby-Bauer’s disc diffusion method by standard CLSI guidelines. HDP showed more specificity (75.77%, HDP + culture positive) than sensitivity (24.22%, culture positive, HDP negative). Gentamycin showed 100% sensitivity. Co-trimoxazol showed 100% resistance from 2008 onwards. T-4 was common phage type been replaced by T-2 by ‘Basu and Mukherjee' scheme while, T-27 was the only predominant one by ‘New scheme’. In 2009, newer phage variants observed. High incidence rate of diarrhea due to V. cholerae is of utmost importance. HDP still has a limited role in diagnosis. Important to study biotype, serotype, phage type and resistogram prevalent in that area for epidemiological control purpose. . Appearance of different circulating phage types in Mumbai, probably originating from different parts of country.